Comparison Of Steroid-Resistant Nephrotic Syndrome Therapy In Children Using Alkylating Agents, Calcineurin Inhibitors, And Monoclonal Antibodies: A Cost-effective Perspective - Widiasta, Ahmedz; Rahadi, Raden Aswin; Bagaskara, Danang Pangestu Gusti; Rachmadi, Dedi; Hilmanto, Dany (Journal Integration of Management Studies, 2025)
Chronic kidney disease (CKD) poses significant medical and economic challenges, particularly in pediatric patients, with steroid-resistant nephrotic syndrome (SRNS) being a major contributor. Despite the financial support provided by Indonesia’s BPJS health insurance system, the rising prevalence of SRNS necessitates a reassessment of treatment strategies. This study retrospectively analyzed pediatric SRNS cases at Hasan Sadikin General Hospital, Bandung, from 2010 to 2019, focusing on the effectiveness and cost-efficiency of different treatment regimens, including calcineurin inhibitors (CNIs) and cyclophosphamide (CPA). Among 2,590 SRNS cases, CPA achieved a remission rate of 48.75%, whereas CNIs demonstrated superior efficacy, with tacrolimus (96.87%) and cyclosporine A (75.61%) achieving significantly higher remission rates in 2018–2019. Although CNIs incurred higher initial costs, they were more cost-effective in the long term. Rituximab (RTX) emerged as a promising alternative, with a 90% remission rate, offering potential savings by reducing disease progression and preventing more expensive treatments associated with advanced CKD. These findings highlight the necessity for a strategic shift in SRNS treatment protocols, emphasizing not only immediate costs but also long-term health outcomes and financial sustainability. Integrating RTX into standard treatment guidelines could enhance patient prognosis while optimizing healthcare expenditures. However, further research is needed to evaluate the long-term health impacts, expand the demographic scope, and refine cost-effectiveness analyses. A comprehensive approach to SRNS management, prioritizing both clinical efficacy and economic viability, is crucial to improving pediatric CKD outcomes and ensuring the sustainability of national healthcare resources.